2011
DOI: 10.1212/wnl.0b013e3182143537
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate for gait impairment in Parkinson disease

Abstract: NCT00526630.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(50 citation statements)
references
References 31 publications
0
47
0
3
Order By: Relevance
“…ppERK/ERK1 values with their corresponding global AIMs over all treatments showing a significant correlation between ppERK1 and dyskinesia severity. Correlation analysis, n = 7, R = .86, P = .003. study), methylphenidate [which also affects NET function (Pan et al, 1994)] tended to increase LID (Devos et al, 2007;Espay et al, 2011). Exacerbation of dyskinesia in a clinical setting may go unnoticed given the absence of baseline readings before DMI administration.…”
Section: Norepinephrine Transporter and L-dopa Dyskinesiamentioning
confidence: 92%
“…ppERK/ERK1 values with their corresponding global AIMs over all treatments showing a significant correlation between ppERK1 and dyskinesia severity. Correlation analysis, n = 7, R = .86, P = .003. study), methylphenidate [which also affects NET function (Pan et al, 1994)] tended to increase LID (Devos et al, 2007;Espay et al, 2011). Exacerbation of dyskinesia in a clinical setting may go unnoticed given the absence of baseline readings before DMI administration.…”
Section: Norepinephrine Transporter and L-dopa Dyskinesiamentioning
confidence: 92%
“…In small open-label studies, the epinephrine precursor L-threo-DOPS was found to have beneficial effects on freezing and gait disturbances in PD patients (Tohgi et al, 1993;Giladi, 2008;Devos et al, 2010). Furthermore, methylphenidate, a mixed dopamine and noradrenaline reuptake inhibitor, was found to show benefit on gait and freezing scores in a randomized controlled trial of 17 advanced PD patients , but results of a more recent trial in 27 PD patients revealed that methylphenidate did not improve gait and tended to worsen measures of motor functions, sleepiness, and quality of life (Espay et al, 2011). Other trials using lower doses of this compound in PD patients with gait impairment are currently underway.…”
Section: Non-dopaminergic Therapiesmentioning
confidence: 99%
“…One pilot study reported significantly improved attention after administration of a single dose of the dopamine reuptake inhibitor methylphenidate, but with no change to memory or visuospatial performance [19]. However, tolerability of methylphenidate is in question as sleepiness and worsened motor function and quality of life were reported with use of this medication in one study [20], and increased heart rate and weight loss in another [21].…”
Section: Mild Cognitive Impairment and Dementia In Pdmentioning
confidence: 99%